Kewenangan Notaris Dalam Pembuatan Tanda Bukti Ahli Waris Pada Peralihan Hak Milik Atas Kapal - Radhyca Nanda Pratama; Liza Priandhini (Jurnal USM Law Review)
The purpose of this study is to determine the authority of a Notary in making proof of transfer of ownership rights to a ship due to inheritance. Ships in the legal context have characteristics and are classified as material rights. In this regard, according to and in line with the principles in the law, objects can be transferred. However, in the transfer of ownership rights to ships that need to be underlined are ships that have been registered and recorded in the Indonesian ship register as evidenced by proof of grosse ownership of the ship registration deed. As for the problem in the transfer of ownership rights to ships due to inheritance in the provisions of the Regulation of the Minister of Transportation of the Republic of Indonesia Number 39 of 2017 concerning Registration and Nationality of Ships, it is only limited to documents determining inheritance from the Court so that in inheritance law practice, especially to make evidence as an heir also involves the role of Notary. The method of writing this article uses normative juridical research. Characteristics of acquiring ownership of a ship can be done in two ways, first through registration of the ship to the Registry Officer and Registrar of the Transfer of the Name of the Ship. Second, through the transfer of ownership rights to the ship, moreover it can also be transferred through inheritance according to law or according to a will. The position of the Notary's role in the transfer of ownership rights to the ship due to inheritance actually has the authority to make a certificate of inheritance even though this authority is traced in other laws and regulations.